Which Dimensions of Human Sexuality Are Related to Compulsive Sexual Behavior Disorder (CSBD)? Study Using a Multidimensional Sexuality Questionnaire on a Sample of Polish Males. Issue 8 (13th June 2019) - Kowalewska, Ewelina; Kraus, Shane W.; Lew-Starowicz, Michał; Gustavsson, Katarzyna; Gola, Mateusz
Abstract: Introduction: Human sexuality is a multidimensional phenomenon related to several factors, such as self-esteem, awareness of sexual needs, and ability to communicate them to others. Aim: To examine the sexual characteristics of patients seeking treatment for compulsive sexual behavior disorder (CSBD)—a clinical diagnosis recently included in the 11th edition of the International Classification of Diseases classification. Methods: We have investigated the sexual characteristics of 72 Polish men seeking treatment for CSBD compared with 208 men from the Polish general population. Main Outcome Measures: The Multidimensional Sexual Questionnaire–PL was used to examine 12 sexual aspects of human sexuality. The severity of CSBD symptoms was assessed using Sexual Addiction Screening Test–PL, and the severity of problematic pornography use was measured by Brief Pornography Screener. Results: Results show that CSBD patients (when compared with the general population) exhibit higher sexual anxiety, sexual depression, external sexual control, and fear of sexual relationship. Furthermore, CSBD severity is negatively related to sexual esteem, internal sexual control, sexual consciousness, sexual assertiveness, and sexual satisfaction. Clinical Implications: Our findings suggest that the impairment of the abovementioned dimensions warrant attention during clinical work and future studies on CSBD. Strengths & Limitations: This study was limited to men, most of whom self-identified as heterosexual. Future research should include women and non-heterosexual identified individuals. Conclusion: Sexual esteem, consciousness, assertiveness, satisfaction and internal sexual control are commonly affected among CSBD individuals and should be properly addressed during the clinical interview and treatment intervention.